BAGAIMANA CARA YANG TEPAT DI DALAM MENGATUR SERTA MENENTUKAN JALAN HIDUP SERTA KARIR KITA KEDEPANNYA? - Wilson, Nicholas (Jurnal Pengabdian dan Kewirausahaan, 2020)
This community service activity was conducted in order to ensure that younger and future generations finally have several insights regarding the importance of determining and setting the career path that they want to achieve in the future from the present time in order to ensure that they won’t get lost in determining what they really want to do during the course of their life. It is mainly because most people, particularly those who are from the younger generations, tend to not have a specific and clear intention of what they want to do, or what they want to achieve in their life, in which, they tend to just follow through with their life without having any clear intentions of what they really want to achieve in their life. Therefore, it is important for the younger generations to fully understand the importance and the crucial aspect of understanding their passion, their interest, or their affection toward certain field that they wish to do, in which, such passion could eventually and potentially become their career which they could develop for the entirety of their life. This community service was conducted virtually through Google Meet because of the current COVID-19 pandemic which hamper the possibility that this community service activity was conducted physically to the participants. Meanwhile, a total of 27 participants who participated in this community service session are senior high school students from Bunda Mulia Senior High School. Furthermore, regarding the completion of this activity, author was hopeful that all participants could finally understand the importance of setting their own objectives and career path that they want to pursue in their life in order to prevent them from experiencing much confusion regarding what kind of job or what they want to do during the entirety of their life.